Editing - Chang, Justin (FilmCraft, 2012)
"Through seventeen exclusive interviews with some of the world's top film editors, this book explores the art of film editing; its complex processes, the relationship with other film practitioners, and the impact of developments in modern editing techniques."--Zadní s. obálky